STRATEGI MEMPERTAHANKAN KELANGSUNGAN EKONOMI RUMAH TANGGA PETANI DI MUSIM PACEKLIK DESA ROMBIYA BARAT GANDING DALAM PERSPEKTIF ILMU EKONOMI ISLAM - Fatimatus Zahroh; Anna Zakiyah Hastriana (Program Studi Ekonomi Syariah, 2024)
Famine seasons are times when crops that have been planted with difficulty do not produce results due to several factors, and one example is a long dry period that causes at least one famine season. In the face of such a situation, some farmers take advantage of opportunities in the famine season or overcome the difficulties that occur in the famine season in various ways. The purpose of this study is to understand the real income received by farming households in Rombiya Barat Ganding Village during the Famine season period. Can income during the Famine season continue until the next planting period, and how farmer households maintain their survival during the Famine period? This research uses methodology by applying qualitative descriptive data analysis techniques, mainly focusing on the case study approach. Data collection is done through observation, interviews, and documentation, with primary and secondary data sources. The study participants consisted of 10 rice farmers. This study examines the real income of farmers in the lean season from the point of view of their income and consumption. The results show that rice farmers can maintain their real income until the replanting period because their consumption patterns are more controlled and the famine season does not hamper their production, so that rice farmers can achieve their survival.